2016
DOI: 10.1002/jemt.22654
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy as a tool to study the adsorption of DNA onto lipid interfaces

Abstract: The Atomic Force Microscopy (AFM) technique appears as a central tool for the characterization of DNA adsorption onto lipid interfaces. Regardless of the huge number of surveys devoted to this issue, there are still fascinating phenomena in this field that have not been explored in detail by AFM. For instance, adsorption of DNA onto like-charged lipid surfaces mediated by cations is still not fully understood even though it is gaining popularity nowadays in gene therapy and nanotechnology. Studies related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The novelty of the system under investigation lies in the ability to tune the solubility of a synthetic polyelectrolyte by changing the ionic strength of the subphase to examine interactions of either its adsorbed or spread layers with a natural polyelectrolyte. This feature strongly distinguishes this system from the usually studied mixed layers of phospholipids and DNA where the lipid solubility is negligible as compared with that of PDAHMAC [ 3 , 12 , 13 , 15 , 16 , 17 , 19 , 20 , 21 , 22 , 23 , 26 , 32 , 33 , 34 ]. The DNA–lipid interactions are mainly considered to be of electrostatic nature, and DNA is attracted to the layer of positively charged groups of the lipid and can penetrate it [ 20 , 21 , 22 , 34 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The novelty of the system under investigation lies in the ability to tune the solubility of a synthetic polyelectrolyte by changing the ionic strength of the subphase to examine interactions of either its adsorbed or spread layers with a natural polyelectrolyte. This feature strongly distinguishes this system from the usually studied mixed layers of phospholipids and DNA where the lipid solubility is negligible as compared with that of PDAHMAC [ 3 , 12 , 13 , 15 , 16 , 17 , 19 , 20 , 21 , 22 , 23 , 26 , 32 , 33 , 34 ]. The DNA–lipid interactions are mainly considered to be of electrostatic nature, and DNA is attracted to the layer of positively charged groups of the lipid and can penetrate it [ 20 , 21 , 22 , 34 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research into the formation of 2D nanostructures attracts a lot of attention [ 1 , 2 , 9 , 10 ]. While many of the systems investigated involve lipid monolayers [ 11 , 12 , 13 , 15 , 16 , 17 , 19 , 20 , 21 , 22 , 23 , 26 , 34 , 51 ], the present work has adopted a novel approach to confine a spread polyelectrolyte film on a subphase of elevated ionic strength to gain insight into the mechanism of DNA interactions that determine surface aggregate formation. The results have shown that various surface properties including the dynamic surface elasticity, surface tension and surface excess exhibit a long induction period only if the initial surface excess of the surface film is in a quasiplateau region and not if the initial surface excess is lower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA adsorption onto likely charged lipid surfaces mediated by divalent cations can also take place. 47 ] The propensity of membrane wrapping around the particles scales with their mutual attraction strength, see ref. 18 and 48-60 for a theoretical viewpoint.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, in order to understand the molecular mechanism behind the CHOL-lipid interactions mediated by cations, we will compare our results with previously obtained in the literature. For instance, the effect of Ca 2+ on π-A isotherms of DPPC/DPPS 4:1 monolayers was studied at the air-water interface [48][49][50].…”
Section: Discussionmentioning
confidence: 99%